972 PULMONARY HYPERTENSION AND EMBRYOLOGICAL REMNANT: WHAT DO THEY HAVE TO DO WITH EACH OTHER? A CASE REPORT. (15th December 2022) - Fumarola, Francesca; Favaretto, Virginia; Collini, Valentino; Pavoni, Daisy; Driussi, Mauro; Imazio, Massimo; Sinagra, Gianfranco
Abstract: Background: Pulmonary hypertension (PH) is defined as a resting mean pulmonary artery pressure of 20 mmHg or above. The importance of identifying the underlying causes of PH is well known for a correct management and treatment. In particular, any cardiac causes, included shunt, must be investigated. Case Summary: A 73-year-old woman presented to the emergency room for asthenia and dyspnea. First line exams as ECG and X-ray were executed resulting normal. Laboratory assessment showed an elevated brain natriuretic peptide at 675 pg/ml and a D-dimer value of 1116 ng/mlFEU (n.v. < 500 ng/mlFEU) so with the suspect of pulmonary thromboembolism a CT-scan with contrast was performed. It was negative for acute thromboembolism, but it revealed an enlarged pulmonary artery (with a diameter of 39 mm), a possible defect of interatrial septum and an anomalous drainage of inferior vena cava (IVC) into the left atrium (LA). A transthoracic echocardiogram confirmed the anomalous drainage of IVC into the LA that appears dilated but was not diagnostic for the interatrial defect. Furthermore, PH was suspected (systolic peak tricuspid regurgitation velocity of 3, 5 m/s, RA area of 24 cm2, tricuspid annular plane systolic excursion/systolic pulmonary arterial pressure of 0.26 mm/mmHg). A 6-minute walking distance was 376 m. The patient completed the exams with a transesophageal echocardiography that revealed an inferior-type caval vein defect and an over-developed Eustachian valve which divides the right atrium (RA) and connect the IVC with the LA directing the blood flow towards it through the inter-atrial septal defect. Discussion: The Eustachian valve is an embryologic remnant at the junction of the IVC and RA. While it typically does not have any pathologic significance, veno-arterial shunting can rarely occur in patients with prominent eustachian valves and atrial septal defects.